(3GdeSJUaj TQM GdfGaYs - (3YHO Gddg Hf CMeO Hf eMehO GdfSaj, CHh GdHQcGJ, MGaX GdOjf , J (B710 (3g` s; (3fGUQ GdOjf CHh GdbGSe eMeO Hf jhSa GdMSfj GdeOfj GdSeQbfOj GdMfaj,J (B656 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CeO ChdjGFg ai GdYGLdI HCfhGY GdfYe hHYO aEf cJGH GdfGaY ai cKQI LhGgQg hGfXe eG EdJbWg ef aQGFO aCLHJ Edi Pdc cJGH GdWgGQGJ s
(3BNQgG (B:s
(3jfJgi HcJGH GdNfKi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1922s
Keywords: (3CUhd Gdabgs